Analisis Usaha Kerupuk Bawang Rizka di Kelurahan Padang, Kecamatan Lubuk Kilangan, Kota Padang: Analysis of Rizka Onion Crackers Business in Padang Besi Village, Lubuk Kilangan District, Padang City - Lamtiar Septriani Silalahi; Syahyana Raesi; M Hendri (Journal of Agriculture and Social Development, 2022)
This study aims to describe the profile of Rizka Padang Besi's onion crackers business and calculate how much income, profits and break-even point of Rizka Padang Besi's onion crackers business. . The research method used is the case study method. To be able to explain the results of the study, the research is presented descriptively. The results showed that the business activities of this business have 11 workers with a direct wage system, this business still uses simple equipment, this business has the Rizka brand with a year product power while for distribution carried out through direct and indirect distribution channels, and businesses This belongs to the source of capital from itself. The business profit gained is Rp. 23,203,706.236. Onion Crackers Rizka's business is already producing above the breakeven point, which is the breakeven point of quantity of 50 units while the breakeven selling point is Rp. 747,090.7.